Hydrodynamic modelling: estuary dynamic implication to morphological changes - Shahirah Hayati Mohd Salleh; Ibrahiem Al-Ani; Khairul Nizam Abdul Maulud; Wan Hanna Melini Wan Mohtar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Estuaries are transition zones between the sea and inland rivers, where oceanic tidal waves and fluvial flows control hydrodynamic processes. However, these natural changes and implications are not thoroughly understood, particularly in tropical estuaries. The interactions between tidal and riverine flows in the Kuala Pahang Estuary were examined using numerical modelling techniques applying TELEMAC2D. Our results model demonstrate that prolonged heavy rainfall significantly impacted water levels in the estuary system during the neap tide cycle. Moreover, the results show that the tidal range and current speed significantly influenced estuary morphological changes. The flood-ebb current can affect sediment transport near the river bank, leading to erosion. Meanwhile, the ebb-flood current significantly affected the bed sediment and suspension in the estuary mouth area while deposition happens during the slack water, either flood or ebb. Our results have a major impact on estuary morphology and sediment transport in the estuary water column, which will lead to a reduction in estuary water quality and the local economy, particularly fisheries.